Bank connections and the speed of leverage adjustment: evidence from China's listed firms. (25th March 2018) - Li, Wenfei; Wu, Cen; Xu, Liping; Tang, Qingquan
Abstract: This study explores the role of bank connections as an important informal institution in debt contracting. Drawing on a sample of Chinese listed firms from 2004 to 2012, we find that bank connections, established through personal networks, asymmetrically affect the speed of leverage adjustment. Bank connections can reduce the marginal costs of leverage adjustment for under‐levered firms. We further find that such connections are especially important for firms with low levels of collateral and young firms, in areas with relatively underdeveloped financial markets, during periods of tight monetary policy, and when there is little competition in the banking industry.